Students’ Understanding on Physics Equations Used in the Experiment - Ign Edi Santosa (Jurnal Pembelajaran Fisika, 2021)
This study investigates the students’ understanding of physics equations used in the experiment. Here 91 students participated in this qualitative study. All of them worked on the experiment to determine the specific charge of an electron e/m. In this case, physics equations are derived to provide the basis of the experimental method in order to obtain the desired value of e/m. Students’ understanding of physics equations was observed through an initial test, their experimental report, and a final test. The final test reveals that many students perceive the equations as a mathematical tool. As a result, about 64 % of the participant states that e/m depends on the variable in the experiment e.g. the current or the accelerating potential. They do not realize that e/m is a constant.Keywords: physics equation, experiment, specific charge, electron.DOI: http://dx.doi.org/10.23960/jpf.v9.n2.202106